Association between frequency of breakfast intake before and during pregnancy and infant birth weight: the Tohoku Medical Megabank Project Birth and Three-Generation Cohort Study - Misato Aizawa; Keiko Murakami; Ippei Takahashi; Tomomi Onuma; Aoi Noda; Fumihiko Ueno; Fumiko Matsuzaki; Mami Ishikuro; Taku Obara; Hirotaka Hamada; Noriyuki Iwama; Masatoshi Saito; et al. (BMC, 2023)
Abstract Background Low birth weight is associated with an increased risk of developing chronic diseases in adulthood, with a particularly high incidence in Japan among developed countries. Maternal undernutrition is a risk factor for low birth weight, but the association between the timing of food intake and infant birth weight has not been investigated. This study aimed to examine the association between breakfast intake frequency among Japanese pregnant women and infant birth weight. Methods Of all pregnant women who participated in the Tohoku Medical Megabank Project Three Generation Cohort Study, 16,820 who answered the required questions were included in the analysis. The frequency of breakfast intake from pre- to early pregnancy and from early to mid-pregnancy was classified into four groups: every day and 5-6, 3-4, and 0-2 times/week. Multivariate linear regression models were constructed to examine the association between breakfast intake frequency among pregnant women and infant birth weight. Results The percentage of pregnant women who consumed breakfast daily was 74% in the pre- to early pregnancy period and 79% in the early to mid-pregnancy period. The average infant birth weight was 3,071 g. Compared to women who had breakfast daily from pre- to early pregnancy, those who had breakfast 0-2 times/week had lower infant birth weight (β = -38.2, 95% confidence interval [CI]: -56.5, -20.0). Similarly, compared to women who had breakfast daily from early to mid-pregnancy, those who had breakfast 0-2 times/week had lower infant birth weight (β = -41.5, 95% CI: -63.3, -19.6). Conclusions Less frequent breakfast intake before and mid-pregnancy was associated with lower infant birth weight.